Manipulation of electrospun fibres in flight: the principle of superposition of electric fields as a control method - Nurfaizey , Abdul Hamid; Stanger, Jonathan; Tucker, Nick; Buunk, Neil; Wallace, Andrew; Staiger, Mark (Springer, 2012)
This study investigates the magnitude of movement of the area of deposition of electrospun fibres in response to an applied auxiliary electric field. The auxiliary field is generated by two pairs of rod electrodes positioned adjacent and parallel to the line of flight of the spun fibre. The changes in shape of the deposition area and the degree of movement of the deposition area are quantified by optical scanning and image analysis. A linear response was observed between the magnitude of movement of the deposition area and voltage difference between the auxiliary and deposition electrodes. A squeezing effect which changed the aspect ratio of the deposition area was also observed to result from the application of symmetric electrical fields. Statistical analysis showed that the deflection and squeezing responses can be thought of as independent control actions. The results from this experiment suggest this particular application of superposition of electric fields could be used as to control the flight path of an electrospun fibre.